Social media marketing and online small and medium enterprises performance: perspective of Malaysian small and medium enterprises - Musa, Haslinda; Ab Rahim, Namirah; Azmi, Fadhlur Rahim; Shibghatullah, Abdul Samad; Othman, Norfaridatul Akmaliah (2016)
This paper aims to investigate the effectiveness of social media marketing (SMM) practices to organizational performance, which focuses on Malaysian small and medium enterprises (SMEs). Quantitative research method approach is applied to study three types of correlations: (1) Brand reputation and image and online SMEs performances, (2) customer engagement and online SMEs performances, and (3) customer brand attitudes and online SMEs performances.Findings revealed that all of the independent variables were significant and have moderate relationship to the online SMEs performances.This study provided a transparent idea, which more clears on true important factors of SMM and online SMEs performances.The results of this study are believed would facilitate and motivate the SMEs in social media practice for marketing activities.Besides contribution to practice, the paper also contributed to the knowledge in internet technology.